Penegakan Sanksi Terhadap Aparatur Sipil Negara yang Melakukan Pelanggaran Disiplin di Lingkungan Pemerintah Kota Denpasar - Ni Luh Sandiani; I Gusti Bagus Suryawan; Ida Ayu Putu Widiati (Jurnal Interpretasi Hukum, 2020)
One of the problems faced by the Indonesian bureaucracy is the violation of discipline by Civil Servants. Therefore, Law No. 5 of 2014 concerning Civil Servantsand PP No. 53/2010 concerning Civil Servant Discipline. Based on this background, this research was conducted with the aim of outlining how the discipline of Civil Servants in Denpasar City Government based on Law No.5 / 2014 concerning ASN and PP No. 53/2010 concerning Discipline of Civil Servants and how to enforce legal sanctions for Civil Servants who commit disciplinary violations within the Denpasar City Government. This research was designed using an empirical approach. This research was conducted directly at the Denpasar City BKPSDM by conducting interviews with the Kasubid Discipline and the Denpasar City BKPSDM Award. The results of this study indicated that the regulation of Civil Servant discipline in the BKPSDM is clearly regulated in the Civil ServantLaw and PP No. 53/2010 concerning Discipline of Civil Servants, and enforcement of legal sanctions at the BKPSDM for ASN who commit violations of discipline are also guided by Law No. 5 of 2014 concerning ASN and PP No 53/2010 concerning Discipline of Civil Servants. These laws and regulations already have clear rules. The causes of discipline violations committed by Civil Servants are that Civil Servantsdo not understand the rules, the leadership does not act firmly, lack of inherent supervision (WASKAT), and lack of appreciation praise for subordinates.